A robust approach to parameterize dislocation glide energy barriers in FCC metals and alloys - Ashraf, Farhan; Castelluccio, Gustavo M. (Springer, 2021)
The mechanical response of metallic materials is controlled by multiple deformation mechanisms that coexist across scales. Dislocation glide is one such process that occurs after bypassing obstacles. In macroscopic well-annealed single-phase metals, weak obstacles such as point defects, solid solution strengthening atoms, short-range dislocation interactions, and grain boundaries control dislocation glide by pinning the scarce dislocation density. This work investigates the dislocation glide energy barrier in face-centered cubic (FCC) metallic materials by considering a crystal plasticity model that computes the yield strength as a function of temperature. The dislocation glide energy barrier is parameterized by three different formulations that depend on two parameters. A Monte Carlo analysis randomly determines all other coefficients within uncertainty bounds identified from the literature, followed by fitting the two energy barrier parameters to experimental data. We consider ten FCC materials to demonstrate that the methodology characterizes robustly the dislocation glide energy barrier used by crystal plasticity models. Furthermore, we discovered a correlation between the glide barrier and the stacking fault energy that can be used as a basis to infer the glide activation energy.